Tribological behavior of particulates reinforced sustainable composites: Effect of composition, load, and sliding speed - Soni, A. (Elsevier B.V., 2022)
Low friction coefficient with good wear resistance makes plastics an extensively researched tribo-material. In the present study, nine different thermoplastic composites of varying compositions were developed by using different types of waste plastics, namely, low-density polyethylene (LDPE), and high-density polyethylene (HDPE) and polypropylene (PP) as matrices, incorporating Rice Husk Ash (RHA) and sand as fillers. The wear behavior as a function of applied loads and sliding speeds were studied. The minimum volume losses at 34.32, 56.87, 68.15, 79.43 and 90.71 (N) were found to 0.02982, 0.03759, 0.04670, 0.05013 and 0.10027 (cm3) for HD70R15S15, HD90R5S5, LD70R15S15, LD80R10S10 and LD80R10S10, respectively. Similarly, for the given sliding speeds of 0.5388, 0.7184, 0.8980, 1.0776 and 1.4369 (m/s), the minimum volume losses were found to 0.04192, 0.04670, 0.03734, 0.10027 and 0.10026 (cm3) for PP90R5S5, LD70R15S15, PP70R15S15, LD80R10S10 and LD80R10S10, respectively. Moreover, the LDPE composites showed a better abrasive wear performance under high load conditions than HDPE and PP composites. The abrasive wear of the composites increases at high sliding speeds. The composite LD70R15S15 and LD80R10S10 showed a good abrasive wear performance at low and high sliding speeds, respectively, while the mixed PP70R15S15 results in minimum abrasive wear at moderate sliding speed. Different wear mechanisms were observed on the worn surfaces. The wear performance depends on the mode of failure and correlates with the mechanical properties. Finally, the obtained abrasive wear results agree with the wear morphologies. Â© 2022 Elsevier B.V.